(untitled) (Research, Society and Development, 2023)
It is very necessary to plan and monitor the vegetation cover areas of a city to know their dynamics of land use and cover. Information on the quantities and kind of change in these areas also are essential to understand the patterns of space organization. The objective of this study was to analyze the space-time variation of the APA Reserva Florestal Adolpho Ducke based on image classifications to observe the changes in the urbanization process of Manaus city. A Case Study was performed to analyze the space-time variation in 1984, 2013 and 2022 using orbital sensors images from the Landsat series processed in the free software QGIS 3.16.10. From the results obtained, it was observed that over 38 years, the APA presented changes in land use and occupation related to vegetation, water resources and urbanized area. These changes occurred both on the interior and the borders, mainly related to the population increase, once these forest fragments are invaded by irregular occupations which removes the vegetation and acts without any urban planning on these preserved areas in Manaus city. However, the concern is how to guarantee the conservation of other fragments without legal support. Thus, it is necessary to improve the environmental and urban norms to preserve the urban forest fragments and the implementation of a better land subdivision, such as proposed in the Manager Plan of Manaus city.